Properties of copper slag concrete - Zhang, Weide (2009)
This report investigated the mechanical properties of high strength concrete incorporating copper slag as fine aggregates. The rising need for alternative fine aggregates substitution of sand is essential due to its high materials cost and the emphasis on sustainable concrete. Copper slag which is a by-product of copper metal extraction process has been selected as the fine aggregate substitution in high strength concrete production.